2022
DOI: 10.1155/2022/2435361
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Art Value and Application of Art Creation Based on the Emotion Analysis of Art

Abstract: The ultimate embodiment of the value of the art creation process is artistic value, which is the embodiment of the greatest value created by art. Art creation is a form of art culture expression. To make their works more cultural and artistic, creators incorporate their personal creative style and ideological concepts. The ultimate expression of the value of the art creation process is artistic value, which is the embodiment of the greatest value of art creation. It provides a useful method for conducting digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The activation functions of the network are 0 f and 1 f , where 0 f is the image algebraic characteristic function: A   , where A is the threshold value when the input image is binarized and processed. 1 f is defined as follows:…”
Section: ( ) ( )mentioning
confidence: 99%
See 2 more Smart Citations
“…The activation functions of the network are 0 f and 1 f , where 0 f is the image algebraic characteristic function: A   , where A is the threshold value when the input image is binarized and processed. 1 f is defined as follows:…”
Section: ( ) ( )mentioning
confidence: 99%
“…The effective design theory of digital art is an important research direction that has received much attention in visual communication design and brand design in recent years [1]. Digital media is now an indispensable part of people's lives due to the rapid development of information technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Value of Design. Beauty is an emotion in the human heart, a strong thing that awakens the beauty in the deep [22]. This is a man's best wish.…”
Section: The Artistic Expression Of Painting Improves the Aestheticmentioning
confidence: 99%
“…The evaluation results revealed that the system could enhance the learning outcomes of the vocational art teaching school. Wang 7 has performed a study on the analysis of the literature on art classification and sentiment analysis. The problem of art emotion analysis was addressed by the implementation of the Python‐grounded ML art emotion analysis approach.…”
Section: Related Workmentioning
confidence: 99%